Wear behavior of aluminium modified cast iron in comparison with conventional gray cast iron - Maleque, Md. Abdul; Shaha, Sugrib Kumar; Razali, Nurul Nadirah (Elsevier, 2018)
Fe-C-Al alloy cast iron contains spheroidal graphite in its microstructure that proves to bring benefits like better hardness, strength, wear and oxidation resistance at room or high temperature. In this work, various characterization methods have been employed to study the characteristics feature of Fe-C-Al and Fe-C-Si cast irons. The fabrication of Fe-C-Al was done by melted raw materials using an induction furnace followed by charged together pig iron and mild steel with ferro-aluminium as a source of Al at 1350 ˚C. The microstructural study was performed using field emission scanning electron microscope (FESEM) after casting process and results showed that less dense graphite produced in the microstructure of Fe-C-Al cast iron compared to Fe-C-Si cast iron. The results from wear and friction test showed that the cast iron containing Al has lower wear rate at higher temperature compared to Fe-C-Si cast iron.